Lemuru fish oil gel as host modulation therapy in periodontal ligaments induced with Porphyromonas gingivalis - W. Widyastuti; Dian Widya Damaiyanti; Dian Mulawarmanti; Cindy Aprilia Sari; Diah Ayu Siwi (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Periodontitis affects approximately 20%–50% of the global population and is caused by gram-negative bacteria, such as Porphyromonas gingivalis (P. gingivalis). Host modulation therapy (HMT) is part of a periodontal therapy that is used as an adjunct to conventional periodontal treatment to reduce tissue damage. Lemuru fish oil containing EPA and DHA can reduce the formation of MMPs and will further increase the number of fibroblasts there by stimulating collagen formation. Purpose: To determine the effect of lemuru fish oil gel on the collagen density and width of the periodontal tissue induced by P. gingivalis and the correlation between these parameters. Methods: Thirty male Wistar rats were divided into five groups. Induction of P. gingivalis was carried out first, then lemuru fish oil gel was applied to the gingival sulcus for 14 days, according to collagen scores in histological preparations using Masson's trichrome (MT). The width of the periodontal ligament was measured with an image raster program in µm. The data were analysed using statistics to test hypotheses using SPSS version 24. Results: Significant differences in the results of the collagen density were observed between groups K- and K+ and groups K+ and P2. Meanwhile, no significant difference was observed between groups K- and P2, P3, P2 and P3 and K+ and P1. The mean values of the periodontal ligament widths were K- (299.61 ± 51.82µm), K+ (425.85 ± 61.54µm), P1 (346.93 ± 33.53µm), P2 (370.15 ± 49.42µm) and P3 (379.6 ± 49.26). Conclusion: Lemuru fish oil can affect the width of the ligament and the collagen density with an optimal concentration of 20%. The correlation between the collagen density and the periodontal ligament width was negative and not significant.